PredicForex. A tool for a reliable market. Playing with currencies - Aguilera Collar, J.; González-Cebrián Toba, R.; Cortés Velasco, C. (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
The Forex market is a very interesting market. Finding a suitable tool to forecast currency behavior will be of great interest. It is almost impossible to find a 100 % reliable tool. This market is like any other one, unpredictable. However we developed a very interesting tool that makes use of WebCrawler, data mining and web services to offer and forecast an advice to any user or broker.
Keywords: data mining; dollar; euro; forex; web crawlers; web services; weka; IJIMAI